Taking ventilatory measurements out of the lab and into the field - Mostad, O. H. (University of Agder, 2023)
BACKGROUND: Measuring ventilation has priorly been limited to physiological laboratory testing, but now wearables allow for measuring in filed settings. The aim of the study was 1) to quantify breathing rate (BR) response during typical training sessions performed by elite endurance athletes, 2) to investigate if breathing rate responds differently than heart rate during two different standardized field sessions in a group of elite cyclists, 3) to investigate the potential implementation of breathing rate as a practical measurement in training for intensity monitoring in cycling. METHODS: Heart rate (HR), BR and power output were quantified in 11 professional cyclists from the Uno-X Pro Cycling Team during at home training and two training camps in Spain during a 6-month period. The participants executed two standardized filed sessions, measuring their internal responses with wearable devices, in addition to power output. RESULTS: Significant increases in HR and BR were observed during the 5x10-minute session, and only significant HR increase during the 7x7-minuets session. Both variables showed tendencies of mean increases in relation to increases in power output in the 7x7-session. HR decreased (180 ± 7 to 177 ± 6) as workload decreased in the 5x10-session, while BR remained the same (59 ± 10 to 59 ± 9). CONCLUSION: This study demonstrates that measuring BR during exercise and can provide valuable information for intensity monitoring in cycling training. These findings suggest that BR could be a practical measurement for monitoring intensity during cycling training, and further research is recommended to explore its optimal applications.